Tinkering in Game Worlds - Nitsche, Michael (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2014)
This essay discusses machinima as a form of media tinkering that combines modifications of technology with content re-mixing. Drawing on parallels to early radio enthusiasts, this essay argues that machinima makers can be understood as digital crafters who use games as production tools as well as cultural reference. Mike Munson’s machinima piece “The Tyrant” (2006), is examined here as exemplary of such combined forms of media re-crafting. Ultimately, the perspective advocated through this analysis demands the inclusion of production processes in our wider understanding of digital art literacy, of which machinima is one manifestation.